Integrated marketing communication model for creating brand loyalty to Japanese cars in Thailand - Sawmong, Sudaporn (My University, 2018)
Thailand automobile market has experienced growth for several years due to worldwide economic growth. The proposed policies present great opportunities for Japanese car companies who have such technologies and willing to invest in an emerging markets region. This research aimed to find the integrated marketing communication model for creating brand loyalty to Japanese cars in Thailand. The quantitative data was collected via questionnaire survey to 460 Japanese car customers in Thailand. The sampling method used the simple random sampling at the department of Land Transport, Bangkok, Thailand. The descriptive statistics applied in this research consist of mean average, percentage and frequency, whereas inferential statistics consisted of confirmatory factor analysis, path analysis and Structural Equation Modeling. The study found that the integrated marketing communication model for creating brand loyalty to Japanese cars in Thailand consisted of car factors, customer psychological factors, integrated marketing communication tools, and brand loyalty. The constructed model developed by this research is consistent with the empirical data and showed the ability to predict value perception to an acceptable degree with a multiple correlation's squares (R2 of 87 %, GFI = 0.96, AGFI = 0.93, Chi-Square = 114.91, DF = 94, P-Value = 0.089, and RMSEA = 0.022. These finding were achieved through better understanding and addressing the Japanese car producer on integrated marketing communication model for creating brand loyalty in Thailand. The practical implication model has been suggested in this paper.
Keywords: Brand loyalty; Integrated marketing communication model; Japanese cars; Thailand